Questioning the Myths: The Role of Institutions on the "Natural Resource Curse" - Colonia Barrenechea, Henry (2013)
What this research tries to explain is the effect of institutional quality on the way to use natural resource endowments by a yearly panel of eighteen Latín American countries from 1996 to 2011. lnstitutional deficiency makes an untoward effect over the way to use natural resource payments which hurt economic growth. Then, there is not properly a "natural resource curse", but a consequence from the institutional quality of countries on the administration of their income.